Multi-organ IgG4-related sialadenitis diagnosed via core needle biopsy: A case report - Shishuo Ma; Xiaojuan He; Weijia Huang (Elsevier, 2024)
Diagnosing Immunoglobulin G4-related sialadenitis (IgG4-RS) remains challenging due to its rarity and similarity to other forms of sclerosing sialadenitis. Controversies persist regarding biopsy approaches. We presented a case with sclerosing sialadenitis in the major salivary glands, pancreatitis, elevated serum IgG4 levels, and core needle biopsy (CNB) revealed lymphoplasmacytic infiltration. This case report aims to raise awareness of the potential use of CNB in suspected IgG4-RS cases, minimizing associated risks compared to open biopsy.